'Still finest wits are stilling Venus Rose': Robert Southwell's 'Optima Deo', Venus and Adonis, and Tasso's canto della rosa. Issue 3 (11th June 2012) - LAWRENCE, JASON
<x xml:space="preserve">Abstract</x> It has been argued, with reference to Venus and Adonis, that Shakespeare is the poet targeted specifically by Robert Southwell in his mournful stanza on love poetry in 'The Author to the Reader'; this essay argues instead that Southwell's remark has a wider application to English poets of the early 1590s. The image of 'Venus Rose' draws attention to Tasso's celebrated canto della rosa (1581), which survives in a manuscript translation attributed to Southwell, although there is a significant shift, where Tasso's carpe diem conclusion is replaced with an invocation to turn to God. It has been suggested that the translation dates from Southwell's time in Rome in the 1580s; this essay favours a later date of composition, arguing that the poet was aware of both Spenser's adaptation of the song, and Daniel's rendering of it in Delia (1592), and that his translation should be read as further evidence of an engagement with contemporary poetry during the Jesuit mission in England. The essay also considers Shakespeare's treatment of the carpe florem motif in Venus and Adonis, arguing for the poet's direct awareness of Tasso's song and the Armida episode, and highlighting his bold reworking of it at the end of the poem.